Profitability Ratio Analysis as a Measuring Tool for Financial Performance Assessment at PT Prasidha Aneka Niaga Tbk for the period of 2017-2021 - Anti Eri Susanti; Haritsah; Rizqi Widi Feirdani; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
Company performance is needed for financial performance appraisal which is carried out by analyzing financial statements so that companies can utilize their resources and to understand company growth, survive, or even fail. This study aims to look at financial performance in terms of profitability, solvency and liquidity ratios at PT Prasidha Aneka Niaga Tbk for the 2017-2021 period. The method used in this study is qualitative with a population using the financial statements of PT Prasidha Aneka Niaga Tbk for the 2020-2021 period. The results of the study show that the financial performance of PT Prasidha Aneka Niaga Tbk for the 2020-2021 period shows that the company is good at using its assets to generate profits and value for shareholders. PT Prasidha Aneka Niaga Tbk performed well in generating revenue, profit and cash flow.